Leg weld fatigue cracks in anhydrous ammonia nurse tanks. (April 2015) - Russell, A.M.; Becker, A.T.; Chumbley, L.S.; Enyart, D.A.
Highlights: In a 2012 accident, a 5500 L anhydrous ammonia nurse tank vented its cargo via a crack in a leg-weld. Side-angle ultrasound inspection was used to examine 532 used nurse tanks' leg welds. A total of 83 indications were detected in 50 of the 532 tanks. Nearly all indications were oriented parallel to the weld line in the welds' heat affected zones. Several factors suggest leg indications result from fatigue cracks, not stress corrosion cracks. Abstract: In an accident in southwest Iowa, USA in 2012, an anhydrous ammonia nurse tank vented its entire cargo of 5500 L (1500 gallons) of liquid ammonia to the atmosphere. Follow-up study of the failed tank revealed a through-crack along a weld used to connect the tank to its running gear. Side-angle ultrasound examinations were performed on 532 used anhydrous ammonia nurse tanks to measure the locations, sizes, and orientations of flaw indications. The tanks examined had manufacture dates ranging from 1952 to 2011. A total of 83 indications were found in or near the leg welds of 50 of these 532 tanks. Several factors suggest that these indications are fatigue cracks, not the stress corrosion cracks more commonly detected in nurse tanks. These findings suggest that roughly 9% of the 200, 000 nurse tanks in the U.S. nurse tank fleet may contain leg-weld fatigue cracks. Nurse tanks are the only large, pressurized packages for hazardous cargo that do not contain manways; thus, their interior walls cannot be inspected for flaws with magnetic particle or fluorescent dye penetrant methods. Since the tank interior is inaccessible, side-angle ultrasound is the only detection method capable of detecting cracks in nurse tanks initiating at both interior and exterior tank surfaces. For this reason, the authors recommend that side-angle ultrasound be considered for use in periodic nurse tank inspections.